Stereodivergent synthesis of 1,3-syn- and -anti-tetrahydropyrimidinones - Morgen, Michael; Bretzke, Sebastian; Li, Pengfei; Menche, Dirk (Organic letters, 2010)
An efficient protocol for the stereoselective synthesis of 1,3-syn and -anti-tetrahydropyrimidinones (syn- and anti-11a) is reported. The modular procedure is based on a stereodivergent cyclization of readily available urea-type substrates (10a) by intramolecular allylic substitution. The cyclization proceeds with excellent yield (up to 99%) and selectivity (up to dr > 20:1), purely based on substrate control. The product pyrimidines can be readily transformed into the corresponding free syn- and anti-amines.